1975
DOI: 10.1021/jf60199a040
|View full text |Cite
|
Sign up to set email alerts
|

Gel filtration and disc gel electrophoresis of tomato pectic substances

Abstract: STEIN, BROWNcesses and eluent volume should be an important factor influencing its displacement.Increasing eluent volume from 25 to 50 ml significantly increased thiamine recovery (mean recovery increased from 90 to 97.5%) and decreased the standard deviation from 2.15 to 1.53 (Table V). Hence, eluent volume is an important factor affecting both the quantity and reproducibility of thiamine recovery from Decalso.Elution to 50 ml requires more reagent and time than for 25 ml. However, the acid-KC1 eluent is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
6
2

Year Published

1979
1979
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
2
6
2
Order By: Relevance
“…In that case the weight average molecular weights would range from approximately 7 x lo5 to 5 x lo6. These values would then be consistent with those obtained by Stein and Brown (1975).…”
supporting
confidence: 90%
See 4 more Smart Citations
“…In that case the weight average molecular weights would range from approximately 7 x lo5 to 5 x lo6. These values would then be consistent with those obtained by Stein and Brown (1975).…”
supporting
confidence: 90%
“…In that case the weight average molecular weights would range from approximately 7 x lo5 to 5 x lo6. These values would then be consistent with those obtained by Stein and Brown (1975).Fishman et al. (1984) showed that the radii of gyration of pectin molecules were significantly affected by the degree of methylation, with 57% being an o p timal value where steric hindrance would prevent further aggregation.…”
supporting
confidence: 88%
See 3 more Smart Citations